2000
DOI: 10.1002/jlb.67.2.226
|View full text |Cite
|
Sign up to set email alerts
|

Particulate adjuvants can induce macrophage survival, DNA synthesis, and a synergistic proliferative response to GM-CSF and CSF-1

Abstract: The mode of action of immunological adjuvants is not yet completely understood. Many are particulate. Certain antigen-presenting (dendritic) cell populations belong to the monocyte/ macrophage lineage and, like other members of the lineage, in some tissues appear to be short-lived. We report that many poorly degradable, particulate adjuvants, for example, aluminum hydroxide, oil-in-water emulsions, calcium phosphate, and silica, enhance murine bone marrow-derived macrophage survival; induction of DNA synthesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
35
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 28 publications
4
35
0
Order By: Relevance
“…The depot effect is considered an important feature by trapping the antigen at the site of administration and by attracting various kinds of cells, including APC and macrophages [45]. Both alum and oil-based emulsions can be efficiently endocytosed by APC eventually leading to an enhanced proliferative response of macrophages and other cells [46]. Whereas alum results in a moderate depot effect, oil emulsions generate a more pronounced depot [45].…”
Section: Discussionmentioning
confidence: 99%
“…The depot effect is considered an important feature by trapping the antigen at the site of administration and by attracting various kinds of cells, including APC and macrophages [45]. Both alum and oil-based emulsions can be efficiently endocytosed by APC eventually leading to an enhanced proliferative response of macrophages and other cells [46]. Whereas alum results in a moderate depot effect, oil emulsions generate a more pronounced depot [45].…”
Section: Discussionmentioning
confidence: 99%
“…A deposit is formed on injection of alum into tissue, leading to tissue damage, phagocytosis by antigen-presenting cells and possibly the release of danger signals [140]. Furthermore, it has been shown that phagocytosed alum increases the survival of macrophages [141]. Similar fi ndings were found with a number of other particulate adjuvants, including oil-inwater emulsions and calcium phosphate, suggesting that this process may contribute to the effi cacy of particulate adjuvants.…”
Section: Alummentioning
confidence: 64%
“…TiAlV and CoCr particle-treated BMM were larger and more vacuolated than untreated cells and contained particles. When BMM were treated with particles in the presence of suboptimal CSF-1 concentrations, 23 an additive effect was seen (data not shown).…”
Section: Resultsmentioning
confidence: 93%
“…We showed that a number of poorly degradable particulates have a prosurvival activity on monocytes/ macrophages [22][23][24][25][26] ; metallic wear debris can now be added to this list. With regards to mechanism, we recently implicated the antiapoptotic protein Bcl-2 in the prosurvival activity of one of these other particulates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation